Drone technology and performance of retail logistics - Michael Wanjala Muricho; Conrad Ochego Mogaka (Journal of Sustainable Development of Transport and Logistics, 2022)
The purpose of this research study was to explore drone technology and performance of retail logistics by offering academic and practical benefits, explaining the preceding, and recommending a research plan based on a conceptual framework for drone technology and performance of retail logistics. A literature review has been created to assist today's retail logistics managers and researchers in scrutinizing what has been previously researched and what needs to be explored. From the standpoint of retail logistics, the study adds to our knowledge of drone technology as it relates to the performance of retail logistics and the constraints of future research. This study utilized a systematic literature review to design a suggested conceptual framework for a research agenda on drone technology and performance of retail logistics. The research paper provides insights into deficiencies in the drone technology, along with performance of retail logistics literature. The research paper explicitly recommends exploring the drone technology as it relates to expected and actual performance of retail logistics. This article contributes to the literature in a number of ways. To begin with, it provides the first comprehensive succinct synopsis of the essential concepts in the drone technology and retail logistics. Second, the impact of retail logistics in the growth of the economy. Third, the application of drone technology in retail logistics. Fourth, unnoticed challenges in retail logistics are then exposed as ideas for potential research. Finally, the technique utilized to conduct the systematic literature review can be used as a model for prospective researchers when conducting similar research. Contemporary research is aimed at providing a research group that address the needs of adopting the current technology on the performance of retail logistics. For performance of retail logistics, the article presents a suggested conceptual framework for drone technology and performance of retail logistics.